OKR (Objectives and Key Results)-Based Performance Management in Improving Organizational Effectiveness - Andi Makkulawu Panyiwi Kessi (PT. Hafasy Dwi Nawasena, 2026)
Effective performance management is crucial for improving organizational effectiveness, and one of the widely used systems is Objectives and Key Results (OKR). This study aims to analyze the implementation of OKR in enhancing organizational effectiveness, as well as the challenges and solutions encountered in its implementation. Using a Systematic Literature Review (SLR) approach, this research analyzes various studies related to OKR published in the last five years. The findings indicate that the application of OKR can enhance transparency, accountability, and employee engagement in achieving organizational goals. However, the most common challenges are communication gaps and unclear objectives. Organizations with a work culture that supports change and openness find it easier to successfully implement OKR. This study also finds that OKR implementation has the potential to foster a more proactive and accountable work culture. Therefore, OKR is not just a performance measurement system but also a tool for creating a continuous improvement cycle within the organization.